Reliability of Ultrasound Measurements of the Median Nerve in Asymptomatic Subjects Using a Handheld Device - Alfuraih, Abdulrahman M.; Aldahlawi, Rana Hussain; Habib, Yomna S.; Alhowimel, Ahmed S.; Bedewi, Mohamed Abdelmohsen (Sensors, 2024)
This study investigated the reliability of measuring the median nerve cross-sectional area (CSA) at the carpal tunnel inlet using a handheld ultrasound device (HUD) compared to a standard ultrasound system, focusing on intra- and inter-operator reproducibility among novice and expert operators. Employing a prospective cross-sectional design, 37 asymptomatic adults were assessed using both devices, with measurements taken by an expert with over five years of experience and a novice with less than six months. The CSA was determined using manual tracing and ellipse methods, with reproducibility evaluated through intraclass correlation coefficients (ICCs) and agreement assessed via Bland–Altman plots. Results showed a high degree of agreement between the devices, with excellent intra-operator reproducibility (ICC > 0.80) for the expert, and moderate reproducibility for the novice (ICCs ranging from 0.539 to 0.841). Inter-operator reliability was generally moderate, indicating acceptable consistency across different experience levels. The study concludes that HUDs are comparable to standard ultrasound systems for assessing median nerve CSA in asymptomatic subjects, with both devices providing reliable measurements. This supports the use of HUDs in diverse clinical environments, particularly where access to traditional ultrasound is limited. Further research with a larger sample and symptomatic patients is recommended to validate these findings.